Xylo-Oligosaccharide Utilization by Engineered Saccharomyces cerevisiae to Produce Ethanol - Procópio, Dielle Pierotti; Kendrick, Emanuele; Goldbeck, Rosana; Damasio, André Ricardo de Lima; Franco, Telma Teixeira; Leak, David J.; Jin, Yong-Su; Basso, Thiago Olitta (Frontiers in Bioengineering and Biotechnology, 2022)
The engineering of xylo-oligosaccharide-consuming Saccharomyces cerevisiae strains is a promising approach for more effective utilization of lignocellulosic biomass and the development of economic industrial fermentation processes. Extending the sugar consumption range without catabolite repression by including the metabolism of oligomers instead of only monomers would significantly improve second-generation ethanol production This review focuses on different aspects of the action mechanisms of xylan-degrading enzymes from bacteria and fungi, and their insertion in S. cerevisiae strains to obtain microbial cell factories able of consume these complex sugars and convert them to ethanol. Emphasis is given in different strategies for ethanol production from both extracellular and intracellular xylo-oligosaccharide utilization by S. cerevisiae strains. The suitability of S. cerevisiae for ethanol production combined with its genetic tractability indicates that it can play an important role in xylan bioconversion through the heterologous expression of xylanases from other microorganisms.